Industri K-Pop: Pengaruh K-Pop terhadap kebudayaan bangsa Indonesia di era digitalisasi - Cahyono, Ghofur Dwi (Maliki Interdisciplinary Journal, 2024)
K-Pop has had a huge influence on Indonesian society as it became a popular phenomenon. K-Pop culture, music and movies have influenced the lifestyle, fashion and trends of Indonesian teenagers. The strong fanbase, fan commitment and its influence on the economy are evidence of K-Pop’s growing popularity. In addition, K-Pop culture has offered great economic opportunities in Indonesia, as thousands of devoted fans visit K-Pop concerts and are ready to pay top dollar for tickets, official merchandise and other related products.With such dedicated and fanatical fans, K-Pop has become an important part of Indonesian popular culture. They follow all the actions and activities performed by their idol groups, whether through social media, live concerts, or fan events. The Moarmy Pekanbaru community has also witnessed the impact of the spread of popular culture through social media. Some skeptics say that the popularity of K-Pop could blur local cultural identity and replace Indonesian music. Nonetheless, many people see K-Pop as a positive form of cultural interaction, enriching Indonesia’s music and entertainment scene. As such, K-Pop has become a popular phenomenon that has a significant impact on Indonesian society. Among Indonesian teenagers, K-Pop culture has influenced their lifestyle, fashion and trends, and has created significant economic opportunities. Despite criticism, K-Pop has also boosted the music and entertainment industry in Indonesia.